HUBUNGAN INDEKS MASSA TUBUH DENGAN KADAR ASAM URAT PADA WANITA POST MENOPAUSE DI WILAYAH KERJA PUSKESMAS BULELENG III - cindy meilinda sari; I Dewa Ayu Rismayanti; Dewa Putu Agus Erawan; Kadek Supartini (STIKes Buleleng, 2019)
Background : Menopause is a crucial process in reproduction cyclus. One of common physical symptom in menopausal women is obesity. Post menopausel women with obesity have higher risk of arthritis diseases than normal women. Specifically about gout arthritis disease, level of uric acid more than 8 mg/dL. Objective: use to diagnoze. The purpose of this research is to determine the correlation of body mass index and uric acid level in post menopause women in public health center of Buleleng III. Method : This research used correlation analytical research by applying cross sectional approach. The sampling technique used is purposive sampling with 53 respondents who were chosen based on inclusion and exclusion criteria that have been set. Data was collected by GCU easy touch to measure uric acid level. Results :The result of Rank-Spearman test with a confidence level of 95% showed value of p = 0,001( p = 0,05). Conclusion : In conclusion, the result showed there is a significant correlation between body mass index and uric acid level in post menopause women in Public Health Center of Buleleng III.